Hiring Policy in United States Spanish Departments Segmentación académica en departamentos de español en E.U.: Cuestiones de clase social, origen nacional, y etnicidad - Jerry Hoeg; Eric Cohen; Christine Fullen (Arizona State University, 1999)
The present study focuses on two inter-related factors specific to United States college and university Spanish Departments: the unique demographic profile of the entry-level faculty in terms of gender, ethnicity, national origin, and social class; the relation between these factors and hiring practices, especially regarding field of specialization, pay scale, and tenure-track opportunities. We believe these issues are important in that they underscore the value of considering questions of social class as well as ethnicity and gender when analyzing academic job segmentation. El presente estudio pretende enfocar dos factores específicos de los departamentos de español, a nivel universitario, en E.U.: el perfil demográfico de los recién doctorados en términos de sexo, etnicidad, origen nacional, y clase social; la relación entre estos factores demográficos y el nivel de éxito logrado--en términos de campo de especialización, salario, y la posibilidad de lograr permanencia (tenure)--en el intento inicial por conseguir empleo como catedrático en E.U.